Waktu kritis periode lunar dalam menggambarkan status reproduksi ngengat Scirpophaga incertulas (Walker) pada berbagai fase pertumbuhan padi: Critical timing of the lunar period in describing the reproductive status of the Scirpophaga incertulas moth (Walker) on several growth stage of rice - Anggraeni, Flavia Devi; Anwar, Ruly; Ratna, Endang Sri (Jurnal Entomologi Indonesia, 2025)
The yellow stem borer, Scirpophaga incertulas (Walker) is a major nocturnal pest of rice. Presence of S. incertulas moth had a flight peak during the lunar period and affects its reproductive status. The purpose of this study was to analyze the critical time in the lunar period related to the highest reproductive status of S. incertulas in the field. Monitoring of moth populations were carried out by setting up two traps equipped with 60-watt LED lights (800 lm) on farmers’s fields in Rawamerta District, Karawang Regency, West Java. Moth trapping was carried out once an hour, started 6–10 PM, for three days on lunar period. The observation were conducted during the nursery, maximum tillering, and grain filling phases. upen capture, females were transferred to rearing cages until they laid all their eggs. Moth reproductive status, fecundity, and fertility were counted and analyzed. Total of captured female S. incertulas moths in the lunar period from three phases of rice was 216 individuals. In the nursery phase, the highest population level was obtained at 8 PM at 27.8%, While the maximum tillering and grain filling phase were 39.3 and 29.1% at 7 PM. The highest population level of virgin, mating, and post-oviposition moths was obtained at 7 PM, at 10,94, 12,52, and 9,64%. The highest average fecundity occurred at 6 PM with 42 eggs/group and the highest fertility was 45,8% at 8 PM. The highest critical reproductive time of female S. incertulas moths occured between 6–8 PM.